2023
DOI: 10.29333/pr/12566
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate students’ use of social media in school: A need for regulatory policies in Nigerian universities

Abstract: Social media/networks have proven to improve learning and overall students’ progress in their programs when properly used. However, social media have been strongly criticized for its strong negative impacts on students’ performance in their studies. This study, therefore, explored the regulatory policy options to effectively manage students’ use of social media/networks in Nigerian universities. The study used a mixed-method design for the collection of appropriate data to address the objectives. The populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…It was found that most of the 22 articles studied (13 articles) were published between 2019 and 2022. This finding can be explained by the rapid growth of communication technologies among university students and the need to research to examine the effects of SNS on achievement (Astatke et al, 2021;Nannim et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that most of the 22 articles studied (13 articles) were published between 2019 and 2022. This finding can be explained by the rapid growth of communication technologies among university students and the need to research to examine the effects of SNS on achievement (Astatke et al, 2021;Nannim et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid growth of communication technologies, social networking sites (SNS) such as Facebook, Instagram, LinkedIn, and Twitter have become very popular for connecting with others worldwide (Alfaris et al, 2018;Hossain, 2017;Mark et al, 2023;Owan et al, 2020). With the increasing popularity of SNS among university students, the education systems need to adapt their teaching and learning approaches according to SNS to provide students with helpful information and build learning communities in online learning environments at higher education levels (Gilemkhanova, 2019;Nannim et al, 2023). SNS helps students interact with peers or others, share information, and meet with experts in a particular field to expand their knowledge connections and networks in online environments (Gafarov et al, 2021;Hussain et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martinez-Prather and Vandiver (2014) came to the same conclusion as this study, reporting that 20% of the teenagers posted photographs or videos of themselves wearing only pants. Nannim et al (2023) asserted that teenagers used their mobile phone, computer, or other digital device to send, record, and send sexually explicit messages, images, or videos on social media. Results of this study showed that children who use social media often experience loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…The above can also be done similarly for those who choose to access online resources, by leveraging ICT and various social media platforms. Nannim et al (2023) and Banjoko et al (2023) listed YouTube, Facebook, WhatsApp, LinkedIn, ResearchGate and Academia as commonly used social media platforms that students use regularly. This education can help users make informed decisions about their online behaviour and understand the potential risks and consequences of unethical behaviour.…”
Section: Role Of Libraries and Librarians In Curbing Inappropriate Cy...mentioning
confidence: 99%